Mutation of the Glucosinolate Biosynthesis Enzyme Cytochrome P450 83A1 Monooxygenase Increases Camalexin Accumulation and Powdery Mildew Resistance - Liu, Simu (Front Plant Sci, 2016)
Small secondary metabolites, including glucosinolates and the major phytoalexin camalexin, play important roles in immunity in Arabidopsis thaliana. We isolated an Arabidopsis mutant with increased resistance to the powdery mildew fungus Golovinomyces cichoracearum and identified a mutation in the gene encoding cytochrome P450 83A1 monooxygenase (CYP83A1), which functions in glucosinolate biosynthesis. The cyp83a1-3 mutant exhibited enhanced defense responses to G. cichoracearum and double mutant analysis showed that this enhanced resistance requires NPR1, EDS1, and PAD4, but not SID2 or EDS5. In cyp83a1-3 mutants, the expression of genes related to camalexin synthesis increased upon G. cichoracearum infection. Significantly, the cyp83a1-3 mutant also accumulated higher levels of camalexin. Decreasing camalexin levels by mutation of the camalexin synthetase gene PAD3 or the camalexin synthesis regulator AtWRKY33 compromised the powdery mildew resistance in these mutants. Consistent with these observations, overexpression of PAD3 increased camalexin levels and enhanced resistance to G. cichoracearum. Taken together, our data indicate that accumulation of higher levels of camalexin contributes to increased resistance to powdery mildew.